Performance Analysis of Depok City Health Office in Supporting Child-Friendly City - Juwono, Vishnu; Damara, Bintang Cynthia (Jurnal Bina Praja, 2020)
Government has to pay attention to the fulfillment of children's rights because later they will determine the fate of the nation and state in the future. One of the things that can be done by the Government is by organizing a Child-Friendly City. One significant cluster related to the implementation of a Child-Friendly City is a cluster of essential health and well- being. The Depok City Government through the Health Office has made various efforts to support the realization of a Child-Friendly City in the health sector. The research method used in this study is qualitative with a post-positivist approach. Based on the results of the study, through the target approach in measuring organizational effectiveness by S. B Lubis and Martani Huseini, the Health Office has exceeded the goals set out in the Medium Term Development Plan. The achievement of these targets is inseparable from the factors that influence the organization in carrying out its performance. Based on McKinsey's theory, seven factors influence the Health Office to support Child-Friendly Cities, two of which have gone well, namely, the leader who motivate their subordinates and the budget and technology that supports the implementation of Child-Friendly Cities. But the other five factors have not gone well, namely the Health Office does not yet have a specific strategy related to Child-Friendly Cities, coordination that has not run optimally, lack of Human Resources both in terms of numbers and competencies and the absence of organizational culture specifically for the Office of Health in carrying out its functions. Therefore, the Health Office needs to make improvements from the factors that have not gone well so that Depok City can be a Child- Friendly City. Keywords: Child-Friendly City, Health Office, Depok City, Children's nutritional status, 7s Model